Ajaran Adat dan Pusaka Penghulu dalam Pantun Adat Minangkabau karya N.M. Rangkoto - Yosi Wulandari; Fitri Merawati (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
The culture of pantun has long been a part of the communication characteristics of the Minangkabau tribal community. Pantun is used in daily activities or traditional ceremonies in the past so that many rhymes can be traced and studied about the traditional teachings in them. The purpose of this study is to describe the traditional teachings and heritage of the penghulu in Minangkabau traditional pantun. This research method is descriptive qualitative. The object of research that becomes the focus of this research is the traditional teachings and the heritage of the penghulu. Data were collected using reading and note-taking techniques and analyzed based on data groups of traditional teachings and penghulu. The results of this study show that Minangkabau traditional teachings are based on harmonious relations between customs and religion, teach important things in saying, and have a variety of laws that are used according to the basis and interests that the community must know. In addition, the most important heritage of the penghulu is the reference used by the penghulu in leading the people, namely holding on to customs and religion.